Portraying Students’ Speaking Foreign Language Anxiety Level during Online and Offline Learning - Elbalqis, Putri; Pradana, Satria Adi (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of this present research was to find out the students’ speaking foreign language anxiety level during the online and offline learning. The participants involved in this research were 28 students of junior high school students in SMP Insan Mandiri Bandar Lampung. This research was in descriptive qualitative design. The data were collected by using speaking foreign language anxiety questionnaire adopted from Ozturk (2014). The questionnaire form was in 5-graded likert scale, the data were analyzed by classifying the results using the range levels guideline adopted from Ozturk (2014). The results from the questionnaire showed that: during the online learning, most of students were in the moderate level of speaking anxiety, and a few students categorized in the high level of speaking anxiety. Meanwhile, after the pandemic era where the students got the limited offline learning, it was found that the majority of students were still on the moderate level of speaking anxiety, but there was no student categorized in the high level of speaking anxiety.